Breaking the paradigms of residual categories and neglectable importance of non-used resources: the "vital" traditional knowledge of non-edible mushrooms and their substantive cultural significance - Amaranta Ramírez-Terrazo; E. Adriana Montoya; Roberto Garibay-Orijel; Javier Caballero-Nieto; Alejandro Kong-Luz; Claudia Méndez-Espinoza (BMC, 2021)
Abstract Introduction One of the main goals of ethnomycological studies has been understanding the role of wild edible mushrooms (WEM) in diverse cultures. To accomplish such a purpose, the local knowledge of WEM and their cultural importance have been evaluated and compared using qualitative and quantitative methods. However, few studies have documented these aspects in non-edible mushrooms, because they are considered to be in a category of residual cultural importance. To make up for this lack of investigation, this paper analyzes the traditional knowledge of non-edible mushrooms to understand their cultural role and break it down to its components. The analysis of this topic shows how this knowledge represents a good strategy to prevent mushroom intoxications in humans. Methods This study was carried out in two communities residing in La Malintzi National Park, Tlaxcala, Mexico. Mushroom species indicated as non-edible were collected during 13 ethnomycological expeditions and seven requests. To get an insight into the local knowledge about these mushrooms, we used ethnographic techniques, 91 free listings and 81 semi-structured interviews. Results In total, we collected 178 specimens of wild mushrooms recognized as non-edible by locals, which corresponded to 103 species belonging to 45 genera. People who participated in the study had a vast and deep understanding of non-edible mushrooms. For them, the most important species were Amanita muscaria, Neoboletus aff. erythropus, Xerocomellus chrysenteron, and Suillus tomentosus. Two uses were the most mentioned by respondents: as an insecticide and for medicinal purposes. Of note, however, is that A. muscaria was reported as edible years ago. To avoid possible intoxication, all non-edible mushrooms were included in the general category of "poisonous mushrooms." Non-edible species are seen as a cosmogonic counterpart ("twins") of the edible species that they resemble. We obtained 101 specific recognition criteria, useful only when comparing paired species: edible vs non-edible. The most culturally important non-edible groups were differentiated by clear and precise characteristics, which were reflected in the nomenclature and allowed their classification into specific ethnotaxa. Conclusions We found that non-used resources can be the object of a deep traditional knowledge and have a vast cultural importance. In the case of wild non-edible mushrooms in particular: the species are named; they are the subject of vast traditional knowledge which is based on their edible/non-edible duality; this knowledge is widespread but has limited consensus, there is little lexical retention; and this knowledge is vital to avoid fatal intoxications. In consequence, both deadly species and species that share similarities with the most important edible mushrooms have a high cultural importance.